Spatial and Temporal Variation of Phytoplankton Production in Lake Michigan - (:unkn) unknown (My University, 2018)
Although many studies have documented decreases in phytoplankton production since the quagga mussel invasion, we currently have a limited understanding of the spatial variation and temporal dynamics of phytoplankton production in Lake Michigan. In this study, phytoplankton production and seston stoichiometry were measured bi-weekly near Milwaukee, three times at two northern basin sites, and along three nearshore-offshore transects from May to November 2017, as well as at 5-6 sites on three whole-lake surveys in 2016 and 2017. Estimates of growth rates were calculated from phytoplankton production and carbon measurements. In spring 2016 and 2017, growth estimates were similar across the lake and no single factor appeared to control production perhaps because temperature, light, and nutrients were all limiting. In summer 2017, production, biomass, and growth estimates all increased from south to north following the trend in decreasing nutrient limitation. Nearshore production was generally greater than offshore production, but nearshore-offshore patterns were highly dependent on upwelling. Temporally, areal production peaked in August and September with the warmest temperatures, and temperature was the only variable significantly related to production and growth estimates. Mean summer production in 2017 (473 mg C m-2 day-1) was lower than the mean summer production from prior to the mussel invasion in 1983 to 1987 (867 mg C m-2 day-1; Fahnenstiel et al., 2010). Deep chlorophyll layer (DCL) production also decreased from 30% of total water column production in the 1980s (Fahnenstiel et al., 1987a) to 17.3% of measured total water column production in 2017. Phosphorus limitation, light harvesting capabilities, light saturated maximum photosynthetic rates, and growth estimates of DCL and epilimnetic phytoplankton have not changed since the mussel invasion despite decreasing total phosphorus concentrations, suggesting the decrease in phytoplankton production in Lake Michigan is due primarily to grazing by mussels rather than increased nutrient limitation.
Keywords: DCL; Great Lakes; Nearshore; Photosynthesis; Phytoplankton; Zooplankton